Behavioral and biochemical evidence of the role of acetaldehyde in the motivational effects of ethanol - Peana, Alessandra T.; Acquas, Elio (Frontiers in Behavioral Neuroscience, 2013)
Since Chevens’ report, in the early 50's, that his patients under treatment with the aldehyde dehydrogenase inhibitor, antabuse, could experience beneficial effects when drinking small volumes of alcoholic beverages, the role of acetaldehyde (ACD) in the effects of ethanol has been thoroughly investigated on pre-clinical grounds. Thus, after more than 25 years of intense research, a large number of studies have been published on the motivational properties of ACD itself as well as on the role that ethanol-derived ACD plays in the effects of ethanol. Accordingly, in particular with respect to the motivational properties of ethanol, these studies were developed following two main strategies: on one hand, were aimed to challenge the suggestion that also ACD may exert motivational properties on its own, while, on the other, with the aid of enzymatic manipulations or ACD inactivation, were aimed to test the hypothesis that ethanol-derived ACD might have a role in ethanol motivational effects. Furthermore, recent evidence significantly contributed to highlight, as possible mechanisms of action of ACD, its ability to commit either dopaminergic and opioidergic transmission as well as to activate the Extracellular signal Regulated Kinase cascade transduction pathway in reward-related brain structures. In conclusion, and despite the observation that ACD seems also to have inherited the elusive nature of its parent compound, the behavioral and biochemical evidence reviewed points to ACD as a neuroactive molecule able, on its own and as ethanol metabolite, to exert motivational effects.